FRI0223 Long-term targeted safety event rates in ra patients following initiation of rituximab: interim analysis from sunstone registry. (23rd January 2014) - Furst, D.; Winthrop, K. L.; Alexander, K. A.; Vashishtha, A.; Francom, S. F.; Saag, K. G.
Abstract : Background: Rituximab (RTX) is used for the treatment of rheumatoid arthritis (RA) in patients (pts) with an inadequate response to anti-TNF therapy. Long-term safety data on real world RTX use in RA are limited. Objectives: To describe the frequency of targeted safety events in an observational cohort of RA pts initiating RTX in the US. Methods: SUNSTONE is a prospective observational cohort study designed to evaluate the safety of RTX in RA pts in the real-world setting. Pts are evaluated and treated according to their physician's standard practice and followed at standard of care visits every 6 mo. All pts were required to receive ≥1 RTX course but could subsequently receive other RA therapies including biologic DMARDs. Pts are assessed at baseline and at follow-up visits every ≤6 mo. Data collection focuses on targeted adverse events (AEs) (significant infections [infections that meet serious AE criteria or require IV antibiotics], cardiovascular thrombotic events, seizures, deaths), and pregnancies. Pts are followed for 5 y (regardless of time of RTX discontinuation) or until death, withdrawal of consent or loss to follow-up. Interim analysis results (Oct 5, 2012) are presented (study completion expected 2014). Baseline demographic and disease characteristics, and safety events captured during follow-up are summarized. For calculating incidence rates, only the 1st event is counted and follow-up is censored at 1st event, as in similar studies [1 -3 ]. Rates per 100 pt-yrs (PY) are reported. The follow-up period includes the entire study period, even after RTX discontinuation or start of another therapeutic agent. Results: Overall, 994 pts (3608 PY) received RTX (82% female; median age 58 y; median disease duration 9 y; 72% RF+). Mean follow-up was 3.6 y; mean number of RTX courses was 3.9; 72% received ≥2 courses. Significant infections were reported in 184 pts, with a corresponding incidence rate of 5.7 (95% CI: 4.9–6.6) per 100 PY. Respiratory, skin/soft tissue and abdominal/gastrointestinal infections were the most common infections observed. No cases of progressive multifocal leukoencephalopathy or tuberculosis were reported. Overall, 60 deaths were reported (1.7/100 PY; 95% CI 1.3–2.1). Cardiovascular disease, malignancy and infection were the most common causes of death. Incidence rates per 100 PY (95% CI) of other safety events were: myocardial infarction 0.6 (0.4–0.9), cerebrovascular accident 0.5 (0.3–0.8), pulmonary embolism 0.3 (0.1–0.5), deep vein thrombosis 0.4 (0.2–0.6) and seizures 0.1 (0.1–0.3). Seven pregnancies were reported. Conclusions: This interim analysis gives a preliminary summary of the frequency of targeted safety events from the SUNSTONE registry of RA patients who had an inadequate response to anti-TNF therapy and initiated RTX treatment. Although impossible to control all methodologic differences between SUNSTONE and other observational studies examining the incidence rates for the events of interest in RA pts, these data appear consistent with rates reported from other studies [1 -4 ]. References: Curtis et al. Ann Rheum Dis 2011;70:1401; Nguyen-Khoa et al. Semin Arthritis Rheum 2012;42:119; Dixon et al. Arthritis Rheum 2007;56:2905; Dixon et al. Arthritis Rheum 2007;56:2896 Disclosure of Interest : D. Furst Grant/research support from: Abbott, Actelion, Amgen, BMS, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: Abbott, Actelion, Amgen, BMS, BiogenIdec, Centocor, CORRONA, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Speakers bureau: Abbott, Actelion, UCB (CME ONLY), K. Winthrop Grant/research support from: Pfizer, Consultant for: Genentech Inc., Pfizer, UCB, K. Alexander Shareholder of: Roche, Employee of: Genentech Inc., A. Vashishtha Employee of: Genentech Inc., S. Francom Employee of: Genentech Inc., K. Saag Grant/research support from: ACR; Ardea; Savient; Takeda; Regeneron, Consultant for: Ardea; Rengeneron; Takeda; Savient